Development of Digital-Based Smart Card Learning Media to Improve the Learning Outcomes of Madrasah Ibtidaiyah Students - Renni Ramadhani Lubis; Nurhamimah Rambe; Pradana Chairy Azhar; Azri Ranuwaldy Sugma; Togue Nana Dipanda Franklin (Program Studi PGMI UIN Salatiga, 2023)
This study aims to develop appropriate and effective digital-based smart card learning media for class II students of Al Hidayah Sidomulyo Private Madrasah Ibtidaiyah (MIS). The background of this study is the lack of use of learning media used in learning Indonesian. Teachers only use lecture methods and learning media that are less supportive. Due to the limited knowledge of teachers in making learning media interesting for students. This type of research is research and development RD (Research and Development). The development model used in this study is the ADDIE model, which has five stages, namely: (a) analysis; (b) design; (c) development; (d) implementation; (e) evaluation. Data collection techniques in this study were non-test techniques, namely observation, questionnaires, and interviews. The data analysis techniques used in this study are (1) analysis of digital-based smart card learning media; (2) analysis of the effectiveness of digital-based smart card learning media. Based on data analysis, it shows that the digital-based smart card learning media developed is feasible and effective for second-grade students and can improve student learning outcomes.